AMAP Assessment 2002: Human Health in the Arctic. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2003)
"This assessment report details the results of the 2002 AMAP assessment of Human Health in the Arctic. It builds upon the previous AMAP human health assessment that was presented in ‘AMAP Assessment Report: Arctic Pollution Issues’* that was published in 1998. The Arctic Monitoring and Assessment Programme (AMAP) is a group working under the Arctic Council. The Arctic Council Ministers have requested AMAP to: • produce integrated assessment reports on the status and trends of the conditions of the Arctic ecosystems; • identify possible causes for the changing conditions; • detect emerging problems, their possible causes, and the potential risk to Arctic ecosystems including indigenous peoples and other Arctic residents; and to • recommend actions required to reduce risks to Arctic ecosystems. The Ministers have placed special priority on the potential impacts of contaminants on the health of Arctic residents, including the combined effects of mixtures of contaminants acting together with other potential stressors. This report is one of five detailed assessment reports that provide the accessible scientific basis and validation for the statements and recommendations made in the second AMAP State of the Arctic Environment report, ‘Arctic Pollution 2002’ that was delivered to Arctic Council Ministers at their meeting in Inari, Finland in October 2002. It includes extensive background data and references to the scientific literature, and details the sources for figures reproduced in the ‘Arctic Pollution 2002’** report. Whereas the ‘Arctic Pollution 2002’ report contains recommendations that specifically focus on actions aimed at improving the Arctic environment, the conclusions and recommendations presented in this report also cover issues of a more scientific nature, such as proposals for filling gaps in knowledge, and recommendations relevant to future monitoring and research work, etc. To allow readers of this report to see how AMAP interprets and developes its scientifically-based assessment product in terms of ...